Model Test and Numerical Simulation of the Mudcake Thickness Effect on the Bearing Capacity of Vertically Loaded Single Piles. (20th August 2020) - Zhang, Ziguang; Cui, Jian; Ma, Maoyan; Xi, Peisheng
Abstract : Mudcake is an important factor affecting the bearing capacity of vertically loaded single piles. The model test and numerical calculation were used to analyse the stress and displacement characteristics of vertically loaded single piles under the conditions of different mudcake thickness and loading capacity. The effect of mudcake thickness on bearing capacity has been analyzed systematically, and its mechanism and changing laws were revealed. Eventually, the concept of the mudcake thickness effect was proposed, which must be considered fully during the construction of mud protection bored piles. The research results have important scientific value and guiding significance for understanding of the influence of pile side mudcake on the bearing capacity of vertically loaded single piles.